Perspective on newborn screening (NBS): evidence sharing on conditions to be included in NBS in Pakistan - Majid, Hafsa; Jafri, Lena; Ahmed, Sibtain; Humayun, Khadija; Kirmani, Salman; Ali, Natasha; Moiz, Bushra; Khan, Aysha Habib; Afroze, Bushra (Journal of the Pakistan Medical Association, 2022)
Abstract Newborn screening aims at detecting treatable disorders early so that the treatment can be initiated to prevent mortality and morbidity. Such programmes are well established in most developed countries, and all newborns are screened for selected metabolic, endocrine and other disorders based on disease epidemiology, testing and treatment availability, efficiency and cost-effectiveness. Even in developing countries, such screening programmes are initiated using heel prick capillary blood collected on filter paper. The current narrative was planned to provide a perspective with evidence in favour of starting newborn screened for different disorders. The programme project should be initiated nationwide, taking one disorder, congenital hypothyroidism, as the prototype and a newborn screening panel can then be extended to include other disorders. A task force should be set up to recommend disorders to be included in the panel, develop the national plan policies, and define procedures to strengthen the testing.